Husholdningernes disponible indkomst understøttes af de økonomiske hjælpepakker til erhvervslivet - Mikkel Bess; Morten Werner (Danmarks Nationalbank, 2020)
– Since the partial shutdown of Denmark following the covid-19 outbreak, the Parliament has passed several temporary compensation schemes to support companies and sustain employment. Based on simulations using the macroeconometric model ADAM, we find that the compensation schemes can strengthen household disposable income by approx. kr. 15 billion in 2020.
Keywords: 330; Coronavirus; Stabilisierungspolitik; Lohnersatzleistungen; Haushaltseinkommen; Dänemark